Antibacterial and Cytotoxic Effects of Urtica dioica Hydro-alcoholic Extract on Causative Bacteria of Mastitis and Epithelial Cells of Bovine Mammary Gland in vitro - Zahra Sakhaie; Amin Jaydari; Ali Forouharmehr; Nemat Shams; Narges Nazifi (Fasa University of Medical Sciences, 2023)
Background & Objectives: Nowadays, owing to positive features of herbal plants, they are widely being applied to treat different diseases. The current study was designed to assess antibacterial activities and cytotoxic effects of hydro-alcoholic extract of Urtica dioica (U. dioica) on causative bacteria of mastitis and epithelial cells of bovine mammary gland in vitro. Materials & Methods: Hydro-alcoholic extract of U. dioica was provided, then minimum inhibitory concentration (MIC)50 and MIC90 of the extract (µg/ml) was determined against both Escherichia coli and Staphylococcus aureus. Finally, after isolation and culture of epithelial cells of bovine mammary gland, cytotoxic effects of MIC50 and MIC90 concentrations of the hydro-alcoholic extract were evaluated using MTT assay during 24 and 48 h. Results: The hydro-alcoholic extract could inhibit growth of both E. coli and S. aureus, with higher inhibitory effect on S. aureus than that of E. coli. For both species, MIC50 concentration was 312.5µg/ml concentration of hydro-alcoholic extract and MIC90 was 39.06 µg/ml.  The results of MTT assay confirmed that viability of the epithelial cells for MIC50 concentration during 24 and 48 h was 68% and 28%, respectively. Additionally, cell viability for MIC90 concentration in 24 and 48 h was 50% and 6 %, respectively. Conclusion: According to our results, it can be concluded that despite bactericidal activity of U. dioica extract, cytotoxic effects was observed at antibacterial levels. Hence, further formulations are required to treat mastitis using this herbal ointment.